Effects of patch size on liana diversity and distributions in the tropical montane evergreen forests of the Nilgiri Mountains, southern India. (November 2014) - Mohandass, Dharmalingam; Hughes, Alice C.; Campbell, Mason; Davidar, Priya
Abstract: We investigate the effect of patch size on liana diversity and distribution in 19 patches of montane evergreen forest in the Nilgiri hills, Western Ghats, southern India. Additionally, we examined how liana species richness and community assemblage in both edge (within 10 m of the forest edge) and interior regions of forest patches respond to patch size, in order to infer the impact of forest expansion or reduction on the liana communities. A total of 1276 woody liana individuals of 15 species were identified, belonging to 10 genera and nine families. Total species richness of lianas was significantly positively related to forest-patch area, both when analysed for the entire patch, in addition to both core and edge regions when examined separately. Species richness of larger lianas also showed a significant positive relationship with increasing forest patch area. Community assemblage varied with respect to forest edge, with shade-dependent species only occurring in interior patch regions, shade-averse species in edge regions, and shade-tolerant species occurring throughout. Disturbance also played a role in determining the response of liana diversity to patch size, with heavily disturbed patches showing no relationship between patch size and diversity, whereas positive relationships exist in low to moderately disturbed patches. The most significant result is the change in liana community composition between small and larger fragments. Many species present in smaller patches are also present in edge zones of larger fragments. This suggests that lianas are important structural components of montane forest ecosystems, and their compositional patterns are possibly driven by succession. Moreover, this study reveals the importance of edge effect and patch size in influencing liana species richness and compositional patterns.